AN ANALYSIS OF THE VISUAL MEANING OF THE @PSIKOLOGIINDONESIA_ INSTAGRAM ACCOUNT AS A MEDIUM FOR MENTAL HEALTH COMMUNICATION FOR GEN Z IN THE DIGITAL AGE - Suci Shinta Lestari; Zimanda Herko Netri; Fenny Anita (Universitas Dharmawangsa Medan, 2026)
This study aims to analyse the visual meanings contained in the content of the Instagram account @psikologiindonesia_ as a medium for communicating mental health messages to Generation Z in the digital age. The study employed a qualitative approach using Charles Sanders Peirce’s semiotic analysis, which comprises icons, indices and symbols. Data were collected through observation of the five posts with the highest levels of engagement published during the research period. The findings indicate that the visual meanings represented in the content of @psikologiindonesia_ consistently convey mental health messages that are educational, reflective and persuasive. The visuals not only depict the realities of Generation Z’s social media life but also encourage self-awareness, emotional regulation and healthy social media behaviour as means of maintaining psychological well-being. The combination of icons, indices and symbols in each post creates strong, systematic and easily understood meanings for the audience. Furthermore, the findings reveal that the content of the Instagram account @psikologiindonesia_ effectively conveys mental health messages through visual elements that are relevant to the needs of Generation Z, amidst the increasing use of social media as a source of mental health education.